Effects of cooking fuel smoke on respiratory symptoms and lung function in semi-rural women in Cameroon. (January 2015) - Mbatchou Ngahane, Bertrand Hugo; Afane Ze, Emmanuel; Chebu, Cyrille; Mapoure, Njankouo Yacouba; Temfack, Elvis; Nganda, Malea; Luma, Namme Henry
Abstract : Background: Indoor air pollution is a major health problem in the developing world. In sub-Saharan Africa more than 90% of people rely on biomass to meet their domestic energy demands. Pollution from biomass fuel ranks 10th among preventable risk factors contributing to the global burden of diseases. Objectives: The present study aimed to determine the prevalence of respiratory symptoms and the factors associated with reduced lung function in a population of women exposed to cooking fuel smoke. Methods: A cross-sectional study was conducted in a semi-rural area in Cameroon. We compared forced respiratory volume between women using wood ( n  = 145) and women using alternative sources of energy ( n  = 155) for cooking. Results: Chronic bronchitis was found in 7·6% of the wood smoke group and 0·6% in the alternative fuels group. We observed two cases of airflow obstruction in the wood smoke group. Factors associated with lung function impairment were chronic bronchitis, use of wood as cooking fuel, age, and height. Conclusion: Respiratory symptoms and reduced lung function are more pronounced among women using wood as cooking fuel. Improved stoves technology should be developed to reduce the effects of wood smoke on respiratory health.